The Hyber-Flexible Course Design Model (HyFlex): A Pedagogical Strategy for Uncertain Times - Naffi, Nadia (Revue internationale des technologies en pédagogie universitaire / International Journal of Technologies in Higher Education, 2020)
In the rush to save the school year during the outbreak of the COVID-19 pandemic, universities around the world had to react fast. This led to an emergency remote teaching that, in many cases, lacked the quality of online learning. Drawing on my concrete experience in graduate course design and facilitation using the hybrid-flexible course design model (HyFlex), also called “formation comodale,” I discuss the great potential and possible pitfalls of this model as an educational strategy in the context of the pandemic and the inevitable digital transformation of educational institutions.